Biotransformation of gallate esters by a pH-stable tannase of mangrove-derived yeast Debaryomyces hansenii - Song, Lei; Wang, Xiao-Chen; Feng, Zhen-Quan; Guo, Yan-Feng; Meng, Guo-Qing; Wang, Hai-Ying (Frontiers in Molecular Biosciences, 2023)
Tannase is a crucial enzyme that finds wide applications in the pharmaceutical industry, feed processing, and beverage manufacturing. Although extensive studies have been conducted on tannases from fungi and bacteria, reports on tannases exhibiting favorable pH stability are relatively limited. In this study, a tannin-degrading strain Debaryomyces hansenii was screened to induce tannase production, and the corresponding tannase coding gene TANF was successfully cloned and expressed in Yarrowia lipolytica. SDS-PAGE analysis revealed that the purified TanF tannase had a molecular weight of approximately 70 kDa. The enzyme demonstrated optimal activity at 40 °C and retained over 80% of its activity in the range of 35°C to 60 °C. Of particular interest, TanF exhibited remarkable enzyme activity at pH 5.0 and retained more than 40% of its relative activity across a wide pH range of 3.5 to 7.0. Furthermore, TanF exhibited broad substrate specificity for gallate esters. The final gallic acid production by TanF from tannic acid achieved 18.32 g/L. Therefore, the excellent properties TanF has been demonstrated to be an efficient tool for the preparation of gallic acid.